VERTEBRAL OSTEOMYELITIS AND EPIDURAL INFECTION BY RHODOTORULA RUBRA - PEKANAN, Patchrin; THANOMKIAT, Wiwatana; SIRIWONGPAIRAT, Pimjai; CHATCHAVALA, Janjira (The ASEAN Journal of Radiology, 2023)
We presented a case with mixed fungal infection of the thoracic spine, involving spinal bodies and posterior epidural space in the pregnant woman. Diagnosis was reached only by needle aspiration biopsy. Articles concerning Rhodoturula Rubra were reviewed.